Eficiência agroeconômica da associação beterraba x caupi-hortaliça sob quantidades de jitirana incorporadas ao solo - Sousa, Daciano Miguel de (Universidade Federal Rural do Semi-Árido, 2017)
This research was carried out at the Rafael Fernandes Experimental Farm, Universidade Federal Rural do Semi-Árido (UFERSA), located in the district of Alagoinha, Mossoró- RN, from September to December 2015. The objective of this work was to evaluate the agroeconomic efficiency of the association of beet and cowpea in different quantities of Merremia aegyptia incorporated to the soil. The experimental design was developed in a randomized complete block with four treatments and five replications. Treatments consisted of four quantities of Merremia aegyptia incorporated into the soil (10, 25, 40, 55 t ha-1 on a dry basis). The intercropping was established in alternating bands of the component cultures in the proportion of 50% of the area for beet and 50% of the area for cowpea, and the plot consisted of four rows of beets alternated with four rows of cowpea, sided by two rows bordering the oleraceous plant on one side and two rows on the other oleraceous plant on the other. In each block two plots were planted with single beet crops (fertilized with 45 t ha-1 of Merremia aegyptia on a dry basis) and of cowpea (fertilized with 47 t ha-1 of Merremia aegyptia on a dry basis) to obtain the efficiency indices of the association. The characteristics evaluated in the beet were: plant height, fresh and dry shoot mass, root diameter, total, commercial and classified yield of roots and dry mass of roots. In green cowpea, green pod length, number of pods per m², yield of green pods, dry weight of green pods, number of green beans per pod, yield of green beans and dry mass of green beans were evaluated. In the evaluation of the consortium the following indices and agroeconomic indicators were determined: land use index, productive efficiency index, canonical variable (Z), gross and net income, rate of return and profitability index. The highest agronomic and economic efficiency of the association of beet with cowpea was obtained in the amount of 55 t ha-1 of Merremia aegyptia incorporated to the soil. Merremia aegyptia is economically viable in the production of beet and cowpea in intercropping
Agroeconomic efficiency of the beet-x-cowpea association under quantities of Merremia aegyptia incorporated into the soil
Keywords: Beta vulgaris; Vigna unguiculata; Merremia aegyptia; Beta vulgaris; Vigna unguiculata; Merremia aegyptia L.; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA